Nanoparticle-based biomolecules in cancer diagnosis, therapy, drug delivery and prognosis - SV, Sowmya; Augustine, Dominic; Hosmani, Jagdish; Pagnoni, Francesco; Reda, Rodolfo; Testarelli, Luca; Patil, Shankargouda (Frontiers in Dental Medicine, 2024)
Nanoparticles have orchestrated a paradigm shift in the landscape of cancer diagnosis and therapy, presenting a multifaceted approach to tackle the intricacies of malignancies. This comprehensive exposition delves deep into the forefront of nanomedicine, elucidating pivotal strategies and innovations primed to metamorphose the domain of cancer management. Methodology: Nanoparticles transcend traditional boundaries, enabling meticulous, site-specific drug release while minimizing systemic toxicity. Intricately designed activation mechanisms, encompassing pH and enzymatic responsivity, along with concentration-dependent strategies, exploit the distinctive attributes of cancer cells, heralding an era characterized by unprecedented therapeutic precision. The pervasive influence of nanotechnology extends to diagnostics, unlocking the realm of early disease detection and personalized treatment. These versatile agents bestow empowering capabilities upon sensitive imaging modalities, affording real-time monitoring and theranostic potential. Results: This exposition showcases the evolution of cutting-edge nanoplatforms, bridging the chasm between diagnosis and therapy, thereby redefining the confines of cancer care. This review elucidates strategies to combat drug resistance, a perennial challenge within cancer management. By targeting efflux transporters, modulating apoptotic pathways, and countering hypoxia-induced resistance, nanoparticles stand at the vanguard of therapeutic innovation, poised to reinvigorate treatment efficacy. Discussion & Conclusion: Moreover, this exposé underscores the imminent clinical translation of nanoparticlebased drugs, accentuating their potential to metamorphose the landscape of cancer management. Liposomal vaccines, nano-pharmaceuticals, and nanochemodrugs, currently navigating the crucible of clinical trials, bear immense promise in advancing the realm of precision medicine. In this epoch of precision medicine, nanoparticle-fueled innovations stand poised to propel cancer diagnosis and therapy to unprecedented peaks.